Sistemas curvos de grafeno e esferas fuzzy - Silva, Deigivan da (2017)
In this work, we developed a complete study on the relativistic Landau model and non-commutative geometry, the latter was derived from level projection, in order to describe curved graphene systems. In developing of the theory, we address the problem of the eigenvalues from the relativistic Dirac-Landau operador on the sphere with a magnetic monopole in its center. The relativistic fuzzy spheres are introduced using the eigenstates of the relativistic Landau levels and we compare it with non-relativistic cases. Under mass deformation, the fuzzy spheres relative to the relativistic symmetric Landau levels change their sizes, however zero-modes there are no variation of size for the corresponding fuzzy sphere. Consecutively we verify that the relativistic Landau model and non-relativistic system of Pauli-Schr odinger are related by gauge transformation SU(2). And nally, the application of the whole theoretical graphene's framework show a simmetric spectrum with respect to its zero energy, and it maintains itself under mass deformation. On the other hand, the in uence of the mass parameters M 6= 0 on the four fuzzy spheres (two for each valley) is such that, if n 6= 0, two of them are enlarged and the other two are diminished, but for n = 0 the fuzzy spheres (at M) do not change their sizes.